How to Write an English Research Introduction? - Warsidi Warsidi (Ethical Lingua: Journal of Language Teaching and Literature, 2017)
This study is librarian analysis which collects the data from books and journal articles. Those articles and books chapters discuss about introductions in terms of their generic structures. The data collections were applied by reading, taking notes for their generic structures, and analyzing them in term of their generic structure models. Then, the data were reported using qualitative approach by describing their patterns. The results showed that there two big categories for their models, involving pattern models and free models. Pattern models dominated in this study because they have been applied seven experts, while free models have been applied by only two people. Therefore, this study suggests that if the journal, which you direct to publish your articles, doesn’t have pattern, you are recommended to apply the patterns as the following: CARS model from Swales, IPS model from Adnan (2011), Slatcher & Pennebaker, and Ball & Vincent.